Acute toxicity of atrazine, endosulfan sulphate and chlorpyrifos to Vibrio fischeri, Thamnocephalus platyurus and Daphnia magna, relative to their concentrations in surface waters from the Alentejo region of Portugal - Palma, P.
Ecotoxicological effects of the herbicide atrazine and the insecticides endosulfan sulphate and chlorpyrifos were evaluated using a test battery comprising aquatic organisms from different trophic levels. According to the categories established in the EU legislation, atrazine can be considered non-harmful for the species tested, while the insecticides can be considered very toxic for the crustaceans. The results of acute toxicity tests showed that the sensitivity of organisms were as follows: Thamnocephalus platyurus > Daphnia magna > Vibrio fischeri. Chlorpyrifos may act as a toxic compound in the aquatic environment of Guadiana River, as it may be detected in water at levels that promote toxic effects.